The Role of Family Care in Providing Nutrition for Children with Stunting: Literature Review - Asriani Bahar (Sean Institute, 2023)
Child malnutrition remains a significant public health challenge in Indonesia, with anemia, protein-energy malnutrition (PEM), obesity, and stunting among the most frequent concerns. Stunting, a chronic form of undernutrition, particularly affects children in developing nations. This study, employing a literature review methodology guided by the PICO framework, identified six articles examining the influence of family care on stunting prevention. Similar to previous research, these studies strongly emphasize the critical role of families in successful stunting interventions. Notably, all articles highlight the family's multifaceted role, which encompasses tasks, responsibilities, relationships, and functions within the household unit. Addressing stunting necessitates a holistic approach, as its causes extend beyond purely health-related factors and are often intertwined with economic instability in developing countries.